Development of an assessment instrument for student engagement in design thinking projects for health innovation - Dikgomo, K.; Hendricks , S.; Mutsvangwa, T. E. M. (South African Journal of Higher Education, 2023)
Student engagement is a dynamic and multifaceted concept encompassing physical, emotional, and cognitive components. Various instruments to assess student engagement exist; however, these are not intended to assess how students engage with one another and with community stakeholders in participatory health projects. Although instruments exist to assess participation and power-sharing in participatory health research projects, none of the available tools are suitable for assessing student engagement in such projects. Accordingly, this study set out to develop an assessment instrument for student engagement in design thinking projects for health innovation. An adapted form of the survey development guide for medical education research was applied. The development process included triangulation of data, which included collating student input from an initial literature informed instrument, an analysis of written reflective reports and a focus group discussion with students enrolled in a master’s level course called Health Innovation & Design (HID), and design thinking practitioner validation. A final assessment instrument for student engagement in design thinking projects is presented. Note that our instrument incorporates the design thinking phases according to the Innovation Design Engineering Organization (IDEO) design thinking approach, an educational definition of student engagement, and recommendations by students, course lecturers and facilitators of the HID course. The instrument can assess engagement in academic and non-academic settings when design thinking is applied for health innovation.